Nutrient management and submergence-tolerant varieties antecedently enhances the productivity and profitability of rice in flood-prone regions. (2nd October 2019) - Gautam, Priyanka; Lal, B.; Nayak, A. K.; Tripathi, R.; Shahid, M.; Meena, B. P.; Singh, Sudhanshu; Srivastava, A. K.
Abstract: Poor productivity of rice in rainfed lowlands is due to complete submergence as it is a major abiotic stress of these regions. For enhancing the rice productivity of these areas, better nutrient management options are required and results may even better when combined with stress tolerant cultivars, even when tested under natural conditions of farmers' field. For supporting the above statement, the effect of nitrogen and phosphorus in graded doses was evaluated for submergence tolerance in controlled conditions and the results obtained were tested and validated at farmers' field in Cuttack, Odisha, India. Shoot elongation, leaf senescence and lodging were lowest with the application of higher phosphorus (60 kg ha −1 ). Highest dose i.e. 100-60-40 NPK kg ha −1 resulted in higher plant survival of all the varieties by 90–170% over no nutrient application, it was also reflected in the higher growth after recovery, leaf greenness, leaf and stem growth, chlorophyll and carbohydrate concentrations and ultimately higher grain yield. At farmers' field, application of basal P, K and post-flood N management practice resulted in overall better performance of Swarna and Swarna-Sub1 showing higher yield attributes leading to 65.7 and 37.9% higher grain yield, over conventional practices followed by farmers. Apart from that results were more positive if post-flood nitrogen was applied as urea foliar spray might be due to quick absorption of N by plant leaves and also spraying helps in removing the silt of flood water sticking to the leaf surface and facilitated the plants to photosynthesize and survive after desubmergence. These cost-effective management options may enhance the productivity and profitability of rice in the flood-prone areas where farmers hesitate to apply nutrients.